Pengaruh kapasitas sumber daya manusia, pemanfaatan teknologi informasi, pengendalian intern akuntansi, dan komitmen organisasi terhadap keterandalan pelaporan keuangan pemerintah daerah (survei pada skpd se-kabupaten kuansing) - sugandi, Joe; Hanif, Rheny Afriana; ', Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to examine the effect of , Human resource capacity, Information technology utilization, Accounting intern control and comitmen organisation. This research is motivated by the fact that the government financial reporting should provide information on reliable and timely in assessing accountability and decision making of various parties. All variables in this research were measured using a likert scale.The data in this study is the primary data obtained from questionnaires distributed directly to the respondents. Data collected from 54 respondents who are working at financial reporting staff in SKPD of Kuansing regency. The method of data analysis used to test the hypothesis is multiple regression analysis using the program SPSS 20 version.The results of this study is showed that capacity of human resources, utilization of technology, internal accounting controls, and comitmen organisation influence to the reliability of financial reporting in Kuansing regency.Keywords: The reliability of financial reporting, Human resource capacity, Information technology utilization, Internal control system and comitmen organisation